Acute gastroenteritis hospitalizations after implementation of universal mass vaccination against rotavirus - Kõivumägi, Kadri; Toompere, Karolin; Soeorg, Hiie; Kallas, Eveli; Jõgeda, Ene-Ly; Huik, Kristi; Lutsar, Irja; group, Rotavirus Study (Eesti Arst, 2020)
Eesti Arst 2020; 99(7):443